Ultrasonic Velocities of Binary Mixtures of Homologous Series of Ethylene Glycol and Glycerol at Different Temperatures: A Comparative Study. (2020) - Kaur, Kirandeep; Juglan, K.C.; Kumar, Harsh; Sharma, Vishal
Abstract: The densities and ultrasonic velocities of binary mixtures of ethylene glycol and glycerol are measured at different temperatures and at frequency of 2 MHz over entire range of mole fraction. Various theoretical models such as Nomoto, Impedance, Junjie, Van Dael and Vangeel have been used to compute theoretical ultrasonic velocities. The average percentage error has been calculated and chi-square test for goodness of fit has also been to check the validity of theoretical models. The deviation from experimental results is interpreted in terms of molecular interactions among the components of the binary mixtures.